Safety status and physicochemical composition of Plaisentif Cheese - Pattono D.; Civera T.; Dalmasso A.; Battelli G.; Gai F.; Peiretti P.G.; Bottero M.T. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
This is the first attempt to describe Plaisentif cheese. Plaisentif is a traditional cheese produced in the Western Alps and obtained from the raw milk of cows fed on pastures during the violet flowering period. This cheese has never been studied. The aim of this work was to evaluate the safety status of milk and cheese and some basic physical-chemical parameters. Samples of milk and cheese at the end of ripening (60 days) were collected from nine Alpine dairy farms. Content of dry matter, protein, fat and ash, as well as pH and water activity (Aw) were evaluated. The microbiological parameters considered were: coagulase-positive Staphylococci, Enterobacteriaceae, Salmonella spp and Listeria monocytogenes. The final mean values of pH and Aw for cheeses were 5.39 and 0.963, respectively. Salmonella spp was found neither in milk nor in cheese. Listeria monocytogenes was found in one sample of milk. Enterobacteriaceae varied between <10 and 3.26 x 104 CFU/ml in milk and between <10 and 8.1 x 104 CFU/gr in cheese. Coagulase-positive Staphylococci varied from <100 to 3.1 x 104 CFU/ml for milk. Three ripened cheeses from different producers showed counts higher than those permitted by the European Regulations. The rise in Enterobacteriaceae could be due to environmental contamination, because some cheese factories, located above 1400 m a.s.l., are used only during the summer period, when sufficient hygiene standards could be difficult to obtain.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)